Evaluation of the association of physical activity levels with self-perceived health, depression, and anxiety in Spanish individuals with high cholesterol levels: a retrospective cross-sectional study - Denche Zamorano, Ángel.; Pisà Canyelles, Jofre.; Barrios Fernández, Sabina.; Castillo Paredes, Antonio Jonathan.; Pastor Cisneros, Raquel.; Mendoza Muñoz, María.; Salas Gómez, Diana.; Mendoza Holgado, Cristina. (PeerJ, 2024)
Background. Hypercholesterolemia is the most common form of dyslipidaemia in the world leading to negative health effects, both physical and mental. Physical activity (PA) can reduce total cholesterol and has positive effects on mental health. This retrospective cross-sectional study analyses the relationships between physical activity level (PAL), self-perceived health (SPH) and mental health. Methods. This study was based on data from the Spanish National Health Survey 2017 (SNHS 2017), with 3,176 Spanish adults with high cholesterol as participants. Nonparametric tests were used as the data did not follow normality. Results. Dependent relationships were found between PAL and SPH, depression and anxiety. Women had higher depression and anxiety prevalences than men, while men were more likely to report being very active, although the proportion of walkers was higher in women. The physically inactive population presented higher negative SPH, depression and anxiety proportions and psychological distress than physically active people.
Keywords: Ejercicio físico; Encuestas de salud; Hipercolesteremia; Salud mental